Characterisation and Parameters Identification of Materials Constitutive and Damage Models: From Normalised Direct Approach to Most Advanced Inverse Problem Resolution. (2017) - Markiewicz, E.; Langrand, B.
Abstract: The paper aims at providing an overview of the research activities performed from the two past decades at the authors laboratory, in the field of the materials characterisation under dynamic loadings (i.e. from 10 –3 s –1 to 10 +3 s –1 for structural crashworthiness and impact applications) and the parameters identification to model their constitutive behaviour and damage. The different testing devices to load the material sample on the expected strain rate range are presented and discussed first, including the different experimental measurement techniques applied to analyse the stress - strain curves. From the normalised direct approach, two different numerical approaches, based on inverse problem resolution techniques, are introduced and discussed: the well-know Finite Element Model Updating method and the most advanced one based on the Virtual Fields Method, that enables to take the full advantages of full-field measurement techniques, such the Digital Image Correlation method. Applications for different materials and models, viscoplastic and damage, are given to support these advanced methods, including the dynamic strength of riveted and welded assemblies.